A qualitative study on the experience of family members of patients with mild to moderate disturbance of consciousness in NICU undergoing physical restraint (NICU轻中度意识障碍患者实施身体约束时家属真实体验的质性研究) - YIN Zhaomin (殷召敏); WANG Fang (王芳) (中西医结合护理)
Objective To understand the true feelings of family members of patients with mild to moderate disturbance of consciousness in neurosurgical intensive care (NICU) when using physical constraint, in order to provide reference for the further formulation of targeted intervention measures. Methods Using the method of qualitative research, semi-structured interviews were conducted with 11 family members of patients with mild to moderate disturbance of consciousness in NICU during physical restraint. The data were coded, analyzed, sorted and summarized according to Colaizzi's seven step analysis method. Results The experience of family members was summarized into four themes: fully supportive emotional experience, negative psychological experience, lack of family members' cognition of physical constraints, and standardizing the process of physical constraints. Conclusion NICU medical staff should pay attention to the true feelings of patients' family members, strengthen interpretation and communication of informed consent of physical restraint, and standardize the use process of physical restraint in NICU patients. (目的 了解神经外科重症监护室(NICU)轻中度意识障碍患者在使用身体约束时家属的真实感受, 为后期制定有针对性的干预措施提供参考。方法 采用质性研究的方法, 对11名NICU轻中度意识障碍实施身体约束患者的家属进行半结构式访谈, 按照 Colaizzi 七步分析法对获得的资料进行编码、分析、整理和归纳。结果 神经外科重症监护室轻中度意识障碍患者实施身体约束时家属的真实体验可归纳为4个主题: 完全支持型情感体验、负性心理体验、家属对身体约束认知缺乏、规范身体约束的流程。结论 NICU医护人员应关注患者家属的真实感受, 做好身体约束知情同意的解释和沟通, 规范NICU患者身体约束的使用流程。)